2017
DOI: 10.3389/fevo.2017.00054
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Correlations Associated with Fear of Humans Differ between Rural and Urban Burrowing Owls

Abstract: Behavioral studies are fundamental to understanding how animal populations face global change. Although much research has centered upon the idea that individuals can adaptively modify their behaviors to cope with environmental changes, recent evidence supports the existence of individual differences in suites of correlated behaviors. However, little is known about how selection can change these behavioral structures in populations subject to different environmental constraints. The colonization of urban enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
51
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 56 publications
(73 reference statements)
6
51
6
Order By: Relevance
“…Thus, it is important to look at behavioral variation on multiple levels (Dingemanse et al, ). Third, the contrast between our results and other recent studies addressing the relationship between responses to humans and to non‐human predators (Carrete & Tella, ; Myers & Hyman, ) suggests that estimating the same trait (e.g., risk‐taking) from different forms of behavior (e.g., aggression vs. avoidance) might yield different results. Therefore, comprehensive studies investigating several behavioral domains at the same time along the urbanization gradient will be important for furthering our understanding of urban adaptations.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Thus, it is important to look at behavioral variation on multiple levels (Dingemanse et al, ). Third, the contrast between our results and other recent studies addressing the relationship between responses to humans and to non‐human predators (Carrete & Tella, ; Myers & Hyman, ) suggests that estimating the same trait (e.g., risk‐taking) from different forms of behavior (e.g., aggression vs. avoidance) might yield different results. Therefore, comprehensive studies investigating several behavioral domains at the same time along the urbanization gradient will be important for furthering our understanding of urban adaptations.…”
Section: Discussioncontrasting
confidence: 99%
“…These two studies notably differ from ours in that they assessed responses to humans through avoidance behavior (flight initiation distances) and responses to non‐human predators through aggression (mobbing), whereas we assessed both behaviors through avoidance (i.e., delaying return to the nest box where the threat appeared). Interestingly, both earlier studies found that behaviors within the same domain (i.e., avoidance vs. aggression) remained correlated even in urban birds: There was a habitat‐independent correlation between avoidance of humans and avoidance of novel objects (Carrete & Tella, ), as well as between aggression toward predators and aggression toward conspecifics (Myers & Hyman, ). Despite focusing on a single domain, however, we found no phenotypic correlation in the risk‐taking in great tits.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This finding is in line with studies showing that urban great tits are more explorative and less neophobic than their rural counterparts (Tryjanowski et al, 2016;Charmantier et al, 2017;Riyahi et al, 2017), and display shorter flight initiation distances (Møller, 2008(Møller, , 2012, which represent other aspects of the proactive coping strategy. Findings on the great tit are also in line with data from other bird species, for which urban populations have also been found to display proactive behaviors (Evans et al, 2010;Carrete and Tella, 2017), but these studies compared few populations (Miranda et al, 2013). Our study included 14 populations from a large geographic area and revealed consistent results across localities, allowing to generalize the impact of urbanization on great tit coping styles.…”
Section: Discussionsupporting
confidence: 84%